2007
DOI: 10.1002/ps.1472
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism of imidacloprid and DDT by P450 CYP6G1 expressed in cell cultures of Nicotiana tabacum suggests detoxification of these insecticides in Cyp6g1‐overexpressing strains of Drosophila melanogaster, leading to resistance

Abstract: Thus, the gap between the supposed resistance gene Cyp6g1 and the observed resistance phenomenon was closed by the evidence that CYP6G1 is capable of metabolising at least two insecticides.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
132
1
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 168 publications
(150 citation statements)
references
References 39 publications
13
132
1
1
Order By: Relevance
“…In only one previous instance has a single P450 been linked to resistance to more than one insecticidal compound. The Drosophila melanogaster P450, CYP6g1, is associated with resistance to neonicotinoids, the organophosphate malathion and organochlorines DDT and methoxychlor (35)(36)(37)(38). Cross-resistance is arguably an unexpectedly infrequent observation, given the broad substrate specificity of P450s to, for example, plant toxins (39,40).…”
Section: Discussionmentioning
confidence: 99%
“…In only one previous instance has a single P450 been linked to resistance to more than one insecticidal compound. The Drosophila melanogaster P450, CYP6g1, is associated with resistance to neonicotinoids, the organophosphate malathion and organochlorines DDT and methoxychlor (35)(36)(37)(38). Cross-resistance is arguably an unexpectedly infrequent observation, given the broad substrate specificity of P450s to, for example, plant toxins (39,40).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, when the genetic switch UAS:GAL4 was used to overexpress different P450s in genetically transformed Drosophila (Daborn et al 2007), other P450s could again confer resistance to DDT (e.g., CYP12D1) but, critically, none of these other P450s has been shown to be correlated with resistance in field-collected strains. Finally, to prove that CYP6G1 can actually metabolize DDT, the enzyme has been expressed in a heterolgous expression system and has been shown to convert DDT to DDD (1,1-dichloro-2,2-bis(p-chlorophenyl)ethane) via dechlorination (Joussen et al 2008).…”
mentioning
confidence: 99%
“…However, it has been shown that TE insertions in the proximity of Cyps can alter their regulation and cause the over-expression of CYP enzymes, resulting in insecticide resistance (Catania et al, 2004;Daborn et al, 2001Daborn et al, , 2002Jouben et al, 2008). TE insertions could therefore also be a source of genetic variability, and the regulatory motifs they provide could be advantageous for organisms in responding to external stimuli.…”
Section: Discussionmentioning
confidence: 99%